If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + -3m = 8 Solving 17 + -3m = 8 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -3m = 8 + -17 Combine like terms: 17 + -17 = 0 0 + -3m = 8 + -17 -3m = 8 + -17 Combine like terms: 8 + -17 = -9 -3m = -9 Divide each side by '-3'. m = 3 Simplifying m = 3
| 3x+8+2=19 | | 28+h=44 | | 35x-1=20x+2 | | 66x+4=-2 | | (8x-12)=6x+8 | | -2x^2-9x+35=0 | | 19+4h=1-5k | | log[2](5x-2)=1 | | (4x-20)x=90 | | 3f+8+4=-23 | | f(4)=5(-4)-1 | | f(2)=5(-4)-1 | | k+14.5=32.5 | | 1x+5=3 | | f(1)=5(-4)-1 | | 2z+2+2z=z+8 | | 1860=8.314(298)(ln(x)) | | 2.5h-15=45 | | f(-3)=5(-4)-1 | | 2z+2+2z=z | | 8x-4=5+7x | | X-3.2=-.8 | | f(-4)=5(-4)-1 | | cos(x)=.6212 | | X-3.2=.8 | | cosx=.6212 | | 12j=660 | | 4-1.2=4.8 | | 1860=8.314(298)lnx | | b-3.5=29.1 | | 0.5x+0.35(70)=35.5 | | 4xy+2x= |